2019
DOI: 10.5194/isprs-archives-xlii-2-w11-209-2019
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Heritage Monitoring by Low-Cost GNSS Receivers: A Feasibility Study for San Gaudenzio’s Cupola, Novara

Abstract: <p><strong>Abstract.</strong> In this study the cupola of San Gaudenzio’s Basilica in Novara, Italy, has been monitored by using two low-cost GNSS receivers located on the East and West side of the spire. Time series of daily solutions for an observation period of about one year have been collected and interpolated by cubic splines. The minimum description length criterion has been used to optimize this interpolation. The results show that the building had an uplift with a maximum amplitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In a few studies, low-cost GNSS receivers have been used for monitoring natural hazards [23,24], engineering structures [25][26][27][28][29], and even crustal deformation studies [30]. Notti et al [24] conducted continuous monitoring of the slope which causes deformations in the Madonna del Sasso Sanctuary in Italy using low-cost GNSS devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a few studies, low-cost GNSS receivers have been used for monitoring natural hazards [23,24], engineering structures [25][26][27][28][29], and even crustal deformation studies [30]. Notti et al [24] conducted continuous monitoring of the slope which causes deformations in the Madonna del Sasso Sanctuary in Italy using low-cost GNSS devices.…”
Section: Introductionmentioning
confidence: 99%
“…Higher uncertainties were obtained in RTK, remaining below 10 mm for both components. In the case of [28], low-cost GNSS instruments (LEA-6T receiver, Tallysman TW3742, and Tallysman 3740 antennas) were used to estimate the movements of an ancient structure (San Gaudenzio's Cupola, Italy) for more than one year. Movements of 2 cm in the vertical direction (during summer) were detected, followed by horizontal movements of less than 0.5 cm due to temperature variations.…”
Section: Introductionmentioning
confidence: 99%
“…Since CR exhibit a nonlinear displacement behaviour, we have interpolated the time series by the cubic splines, assuming that the model residuals are representative of the phase noise. The number of splines (1-3), fitted to the equal temporal subsets, was determined by satisfying the Minimum Description Length criterion [67]. The standard deviations of the model residuals vary between 0.6-0.9 mm for the ascending orbit and between 0.7 mm-1.3 mm for the descending orbit.…”
Section: Insar Resultsmentioning
confidence: 99%
“…In monitoring natural hazards, geodetic instruments are regarded as expensive and are at risk of being damaged, making their use questionable. As an alternative, low-cost GNSS receivers have attracted special attention recently because of the high positioning accuracy achieved over short baselines [7][8][9][10][11][12][13][14][15]. Multi-frequency receivers are compatible with geodetic and low-cost antennas, and can track satellites from all available satellite constellations.…”
Section: Introductionmentioning
confidence: 99%
“…The u-blox LEA-6T GNSS receiver in combination with Tallysman TW3742 and Tallysman TW3740 was used to monitor San Gaudenzio's Cupola in the city of Novara, located in the northwestern part of Italy. Monitoring was carried out for one year, and the results showed that the old structure moved 20 mm in the vertical direction due to temperature changes, while the horizontal movements were smaller, in the range of a few millimeters [14].…”
Section: Introductionmentioning
confidence: 99%